Immunocytochemical staining of breast carcinoma with the monoclonal antibody NCRC 11: a new prognostic indicator. Issue 6472 (23rd March 1985) - Ellis, I O; Hinton, C P; MacNay, J; Elston, C W; Robins, A; Owainati, A A; Blamey, R W; Baldwin, R W; Ferry, B
Abstract : The staining of breast cancer with a new monoclonal antibody, NCRC 11, was studied in a series of 126 women with primary breast carcinoma. Tumour samples embedded in paraffin were tested, and the minimum duration of follow up was five years or to death. Altogether 119 tumours stained positively. There was a strong relation between the intensity of staining, divided on a four point scale, and patient survival. Patients whose tumours exhibited intense staining had an improved survival compared with those with less intensely staining tumours (p less than 0.0001). Staining related weakly to histological grade but not significantly to oestrogen receptor state or the pathological stage of lymph node disease. Mathematical analysis showed the relation to survival to be independent of the other known prognostic factors. Inclusion of intensity of staining with other factors in a prognostic index might permit a more accurate estimation of prognosis in patients with breast cancer.